Implementation of a system of treatment with plasma for gases using a dielectric barrier discharge cell - Mora Mendoza, Eduin Yesid; Santos, Armando Sarmiento; Casallas Caicedo, Francy Mayoli (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The use of the Dielectric Barrier Discharge (DBD) was initiated in Europe for the production of ozone in the treatment of water for human consumption. From then, the number of industrial applications of this kind of discharge has continued increasing. Currently the DBDs are successfully applied to pollution control and polymers surface treatment in order to increase its printability and adhesion. The invention of the glow discharge at atmospheric pressure, which is based on the DBD, also theoretical studies have been conducted to achieve a better understanding of the mechanisms thereof. This paper presents a detailed description of the phenomenon DBD, and describes the development of a system for the study of the treatment with plasma of gaseous media. The functionality of the developed system was verified with air obtaining visible plasma at 12.31 kV and 27.2 kHz. The results obtained in implementation are consistent with those reported in the literature.